Antibody response against gastrointestinal antigens in demyelinating diseases of the central nervous system. Issue Volume 20:Issue11(2013:Nov.) (7th January 2013) - Banati, M.; Csecsei, P.; Koszegi, E.; Nielsen, H. H.; Suto, G.; Bors, L.; Trauninger, A.; Csepany, T.; Rozsa, C.; Jakab, G.; Molnar, T.; Berthele, A.; et al.
<x xml:space="preserve">Abstract</x> Background Antibodies against gastrointestinal antigens may indicate altered microbiota and immune responses in the gut. Recent experimental data suggest a connection between gastrointestinal immune responses and CNS autoimmunity. Methods Antibodies against gliadin, tissue transglutaminase (tTG), intrinsic factor (IF), parietal cells (PC) and Saccharomyces cerevisiae (ASCA) were screened in the sera of 45 patients with AQP4‐seropositive neuromyelitis optica (NMO) and NMO spectrum diseases (NMO/NMO‐SD), 17 patients with AQP4‐seronegative NMO, 85 patients with clinically definite multiple sclerosis (MS), and 48 healthy controls (HC). Results Thirty‐seven percentages of patients with AQP4‐seropositive NMO/NMO‐SD and 28% of patients with MS had at least one particular antibody in contrast to 8% of HC (P < 0.01, respectively). Antibodies were most common (46%) in AQP4‐seropositive myelitis (P = 0.01 versus HS, P = 0.05 versus MS). Anti‐gliadin and ASCA were more frequent in the AQP4‐seropositive NMO‐spectrum compared to controls (P = 0.01 and P < 0.05, respectively). Conclusion Antibody responses against gastrointestinal antigens are common in MS and AQP4‐seropositive NMO/NMO‐SD, especially in longitudinally extensive myelitis.